Tingkat Kekerasan Dan Daya Terima Sosis Jamur Kuping(Auricularia auricula)Yang Disubstitusi Tepung Ampas Tahu - Hidayah, Nur, Rusdin Rauf, STP, MP, Fitriana Mustikaningrum, S.Gz, M.Sc (2016)
Introduction: The prevalence of overweight or obesity cases to reach 3.6% in infants. One of the main causes of obesity much intake of high calories foods and fat also low fiber intake. One of solution for obesity is change the eating habits. The Wood Ear Mushroom is a source of fiber and protein but low cholesterol. Tofu can be used as an ingredient in the manufacture of wood ear mushroom in substituent sausage. Objective: This study aimed to determine the hardness level and acceptability of wood ear mushroom sausage substituted from tofu dregs flour. Methods: This research method is a research experiment with a completely randomized design using the 3 treatment (2,5%, 5% and 7,5%). The hardness level was measured using a testing tool Broxfield texture analyzer and the acceptability is conducted by using One Way ANOVA with a significance level of 95% and if there is influence, will be followed by a test of Duncan Multiple Range Test (DMRT). Results: The results showed that the level of violence ear mushroom sausage is affected by the substitution of tofu waste flour with p = 0,14, the substitution of 7,5% provides the highest hardness wood ear mushroom sausage. Acceptability of wood ear mushroom sausage is affected by the substitution of flour tofu with p = 0,000 in the overall favorite, with the substitution of tofu dregs flour 2,5% a wood ear mushroom sausage most likes by panelists. Conclusion: There is a substitution effect on the making of flour tofu dregs sausage wood ear mushroom on the level of violence. There is a substitution effect of flour tofu dregs of the received power of sausage wood ear mushroom. Keywords: wood ear mushroom, dregs tofu flour, density level, acceptability, sausage wood ear mushroom.